2016
DOI: 10.1080/09588221.2016.1167091
|View full text |Cite
|
Sign up to set email alerts
|

“Are you able to access this website at all?” – team negotiations and macro-level challenges in telecollaboration

Abstract: This exploratory study contributes to the underexplored area of collaborative task formats in telecollaboration. The study investigates how English as a second language (ESL) student teachers in the US and English as a foreign language (EFL) student teachers in Turkey negotiated the design, implementation, and evaluation of technology-based English language learning tasks. The overall pedagogical goal of this spring 2014 project was to provide participants in different educational and institutional settings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…In her 2016 study, Fuchs identified that factors beyond the educational setting itself also limit the use of the ICT teachers have in a developing country. The author conducted a study in order to explore "how English as a second language student-teachers in the US and English as a foreign language student-teachers in Turkey negotiated the design, implementation, and evaluation of technology-based English language learning tasks" (Fuchs, 2016(Fuchs, : 1152. The aim was for the student-teachers to telecollaborate through Google Sites, a shared wiki platform.…”
Section: The Digital Divide In Second Language Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In her 2016 study, Fuchs identified that factors beyond the educational setting itself also limit the use of the ICT teachers have in a developing country. The author conducted a study in order to explore "how English as a second language student-teachers in the US and English as a foreign language student-teachers in Turkey negotiated the design, implementation, and evaluation of technology-based English language learning tasks" (Fuchs, 2016(Fuchs, : 1152. The aim was for the student-teachers to telecollaborate through Google Sites, a shared wiki platform.…”
Section: The Digital Divide In Second Language Educationmentioning
confidence: 99%
“…Another aspect regarding training and development is teachers who are reluctant to the implementation of CALL and who generally receive training from technology enthusiasts (Chamber & Bax, 2006). Therefore, various authors consider that the best way to implement training sessions on ICT would be through collaborative peer work, as opposed to top-down instruction from a technology expert/enthusiast (Kessler, 2006;Fuchs, 2016). Concerning this, Fuchs (2016: 1153) states that telecollaboration, or collaboration through ICT, is a part of CALL training "from which pre-service and in-service teachers can benefit a great deal."…”
Section: The Potential Of Teacher Education To Overcome the Digital Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars have reported the developmental trend from asynchronous communication to synchronous. For instance, in recent years, telecollaboration has advanced into a more mature and diversified stage, involving e-mail, blogs, audio-conferencing, or social networking (Fuchs, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Again, Chinese students, affected by the Confucian culture, are sensitive to other individuals' feelings and care about their face. Fuchs (2016) reported that US students appeared to be more task-oriented instead of relationshiporiented. Perhaps the current study reinforces the cultural stereotype of individualistic and collectivistic culture as Chinese students expressed great concerns about their relationship with the teacher and other students.…”
Section: Teacher's Biodata and Reflectionsmentioning
confidence: 99%